Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1051/0004-6361/201220368
|View full text |Cite
|
Sign up to set email alerts
|

Solar flare X-ray source motion as a response to electron spectral hardening

Abstract: Context. Solar flare hard X-rays (HXRs) are thought to be produced by nonthermal coronal electrons stopping in the chromosphere or remaining trapped in the corona. The collisional thick target model (CTTM) predicts that more energetic electrons penetrate to greater column depths along the flare loop. This requires that sources produced by harder power-law injection spectra should appear further down the legs or footpoints of a flareloop. Therefore, the frequently observed hardening of the injected power-law el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Note that the observed flare, after background subtraction, had a peak GOES flux of B3.8 (1-8Å) and A4.8 (0.5-4Å). The cutoff energy was varied between [1, 3, 5, 7] keV, since the observational value was uncertain (O'Flannagain et al 2013 note that the non-thermal emission extends down to RHESSI's observational limit of 3 keV). Recall that the spectral index δ was time-dependent, so that the electron beam changes in time (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the observed flare, after background subtraction, had a peak GOES flux of B3.8 (1-8Å) and A4.8 (0.5-4Å). The cutoff energy was varied between [1, 3, 5, 7] keV, since the observational value was uncertain (O'Flannagain et al 2013 note that the non-thermal emission extends down to RHESSI's observational limit of 3 keV). Recall that the spectral index δ was time-dependent, so that the electron beam changes in time (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…They occur in active regions and their frequency distribution is similar to large flares. Yet in one important aspect they differ significantly; their spectra above 10 keV (usually interpreted as non-thermal emission) are generally steep compared to large flares; interpreted as a power-law the spectral index of microflares is generally between −5 and −8 (see Benz & Grigis 2002;Krucker et al 2002;Christe et al 2008;Hannah et al 2008a), while for large flares it typically ranges from −2.5 to −4, (Saint-Hilaire et al 2008), although there are some notable exceptions (Hannah et al 2008b;O'Flannagain et al 2013). A recent full review of microflare properties may be found in Hannah et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that thermal emissions are weak early in the impulsive phase in some small events due to a small emission measure (e.g. Hannah et al 2008a;O'Flannagain et al 2013), and that they are weak in so-called cold flares (e.g. Fleishman et al 2011;Masuda et al 2013;Fleishman et al 2016), so that there are times when thermal emissions are relatively less important compared to non-thermal processes.…”
Section: Resultsmentioning
confidence: 99%